Factors Influencing Internal Control over Financial Reporting in Ministry X Government Assistance: A Symbolic Carrier Perspective - Anggraeni, Riawati; Wardhani, Ratna (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Audit findings on government assistance expenditures at Ministry X reveal internal control weaknesses, particularly incomplete accountability reports and inconsistent procedural practices across work units. This condition indicates that the effectiveness of Internal Control over Financial Reporting (ICoFR) is influenced not only by technical mechanisms but also by institutional dimensions. This study aims to analyze symbolic factors affecting ICoFR effectiveness in government assistance programs. Using a qualitative approach, the study applies thematic analysis, constant comparison, and triangulation across implementing, assessment, and review teams. The findings identify four key symbolic carriers: formal regulations, integrity, accountability, and transparency. These factors shape daily routines and compliance patterns. However, when compliance remains predominantly symbolic and administrative rather than substantive, ICoFR effectiveness becomes constrained. This study contributes by demonstrating that limited ICoFR effectiveness is driven not only by technical shortcomings, but also by symbolic compliance embedded within institutional logics.